Economic Risk Exposure of Selected Projects and Risk Attitude of Investors; Evidence from Liberia - GEEGBAE, Geegbae A; GUL, Ejaz (Asian Journal of Empirical Research, 2013)
Thepresent research is about quantifying the economic risk exposure of the projects and willingness of investors to take a chance on an investment of uncertain outcome based on risk attitude. This paper explains typical investment situations of decision makers who do not know with certainty the outcome of their investment and illustrates with probability distribution a way of measuring risk exposure and introduces the use of utility functions to determine a decision maker’s risk attitude. It is concluded from the study that to determine the true value of investments for risk takers, economic analysis must account for increasing marginal satisfaction of higher payoffs with corresponding increases in marginal utility. A firm or institution can use utility theory in a normative or prescriptive role to establish risk policy for investments that support the firm’s or institution’s risk attitude. Overall the paper provides a useful study on economic risk exposure of projects and risk attitudes of investors in Monrovia, the capital of Liberia.